The effect of exercise training on blood lipids: a systematic review and meta-analysis - Smart, N. A.; Downes, D.; van der Touw, T.; Hada, S.; Dieberg, G.; Pearson, M. J.; Wolden, M.; King, N.; Goodman, S. P. J. (Sports Medicine, 2025)
Background: Dyslipidemia is a primary risk factor for cardiovascular disease (CVD). Exercise training (EXTr) improves some lipid markers but not others; the literature is dated and analyses may be underpowered. Objectives: To clarify which lipid markers are altered with ExTr and establish if information size had yet reached futility. Methods: We conducted a systematic review/meta-analysis, with meta-regression, to establish expected effect size in lipid profile with aerobic (AT), resistance (RT) and combined (CT = AT + RT) ExTr. We conducted trial sequence analysis (TSA) to control for type I and II error and establish if information size had reached futility. Results: We included 148 relevant randomized controlled trials (RCTs) of ExTr, with 227 intervention groups, total 8673 participants; exercise 5273, sedentary control 3400. Total cholesterol (TC) MD - 5.90 mg/dL (95% confidence interval (CI) - 8.14, - 3.65), high-density lipoprotein cholesterol (HDL) 2.11 (95% CI 1.43, 2.79), low-density lipoprotein cholesterol (LDL) - 7.22 (95% CI - 9.08, - 5.35), triglycerides - 8.01 (95% CI - 10.45, - 5.58) and very low-density lipoprotein cholesterol (VLDL) - 3.85 (95% CI - 5.49, - 2.22) all showed significant but modest 3.5-11.7%, improvements following ExTr. TSA indicated all analyses exceeded minimum information size to reach futility. CT was optimal for dyslipidemia management. Meta-regression showed every extra weekly aerobic session reduced TC - 7.68 mg/dL and for every extra week of training by - 0.5 mg/dL. Each minute of session time produced an additional 2.11 mg/dL HDL increase. Conclusion: TSA analysis revealed sufficient data exist to confirm ExTr will improve all five lipid outcomes. CT is optimal for lipid management. The modest effect observed may moderate dyslipidemia medication for primary prevention. Prediction intervals suggest TC, HDL, LDL and TGD are only improved in one-quarter of studies.